Longleaf pine masting, northern bobwhite quail, and tick-borne diseases in the southeastern United States. (September 2018) - Patterson, Thomas; Knapp, Paul
Abstract: Although the relationship between oak mast and Lyme disease incidence in humans is established in the Northeastern U.S., mast-disease relationships have not been explored for longleaf pine in the southeastern U.S. Here, we examine if relationships exist between longleaf pine mast and tick-borne disease incidence in humans using climate, wildfire, and northern bobwhite quail ( Colinus virginianus ) data as possible influential variables. We examined the relationship between longleaf pine mast data and tick-borne disease incidence for Lyme, Spotted Fever Group Rickettsia (SFGR), and Ehrlichia chaffeensis (ehrlichiosis) using one-sided Pearson's product-moment correlations at ten individual masting locations and for the entire masting region in the southeastern U.S. Region-wide mast from the previous year were positively correlated with northern bobwhite quail and negatively correlated with Lyme disease. Additionally, northern bobwhite quail were negatively correlated with SFGR and ehrlichiosis, and both drought severity and fire were not correlated with the other variables. We posit the nutrient-rich pine seeds that are a major food source for northern bobwhite quail promote above-average quail populations the following year. As quail diet transitions from seeds in cool months to ground-dwelling insects the following spring and summer, we hypothesize the ability of northern bobwhite quail to consume ticks reduces tick populations and significantly reduces disease incidence in humans. Highlights: First study to examine linkages between longleaf pine cones and tick-borne diseases. Longleaf pine cones benefit northern bobwhite quail. Quail populations potentially feed on ticks, linked to reduced tick-borne disease.